2020
DOI: 10.4038/jsshr.v5i4.57
|View full text |Cite
|
Sign up to set email alerts
|

Business startup motives and growth expectations of micro and small-scale entrepreneurs in Southern Province of Sri Lanka: the mediating role of entrepreneurial orientation

Abstract: New venture creations are vital for the economic growth of any country because of its contribution to employment generation, employment generation, GDP, innovations and value additions. Though a large number of new venture creations occur every year in Sri Lanka, research findings highlighted that a smaller percentage was able to survive. Hence, the number of business establishments cannot be considered as a meaningful indicator of economic growth of the country and the high failure rate is a crucial issue. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Simon-Moya et al, (2016) found that ventures which started based on market opportunity have better survival chances during times of crisis because these are associated with the concept of entrepreneurial orientation, with the dimensions of innovativeness, proactiveness, and willingness to take risks than those were started based on necessity motive. Sriyani et al, (2020) also argued that the EO plays a crucial role in directing the business toward success. Soininen et al, (2012) found that, during and after a crisis, SMEs with higher EO have better chances of survival.…”
Section: Entrepreneurial Orientation (Eo) and Market Orientation (Mo)mentioning
confidence: 99%
“…Simon-Moya et al, (2016) found that ventures which started based on market opportunity have better survival chances during times of crisis because these are associated with the concept of entrepreneurial orientation, with the dimensions of innovativeness, proactiveness, and willingness to take risks than those were started based on necessity motive. Sriyani et al, (2020) also argued that the EO plays a crucial role in directing the business toward success. Soininen et al, (2012) found that, during and after a crisis, SMEs with higher EO have better chances of survival.…”
Section: Entrepreneurial Orientation (Eo) and Market Orientation (Mo)mentioning
confidence: 99%
“…Schumpeter, (1934) defined innovation as the combination of explicit and implicit production components. Covin & Slevin (1986) refer 'innovativeness' or 'innovative orientation' as the propensity to introduce novelties (cited by Sriyani, et al,2020). Innovativeness also defined as 'a firm's capacity to engage in innovation: that is, introduction of new processes, products, or ideas' (Rhee et al, 2010).…”
Section: Innovative Orientationmentioning
confidence: 99%